Fly species on cows around the Tangkoko Nature Reserve, North Sulawesi, Indonesia and their role as zoonotic disease vectors - Meis Nangoy; Erwin Sondakh; Roni Koneri; Upik Kesumawati Hadi (Society for Indonesian Biodiversity, 2022)
Abstract. Nangoy M, Sondakh E, Koneri R, Hadi UK.2021. Fly species on cows around the Tangkoko Nature Reserve, North Sulawesi, Indonesia and their role as disease vectors. Biodiversitas 23: 631-636. Climate and land-use changes in additional to livestock rearing systems play a role in the distribution, species, and population of fly pests, which may pose a risk to humans and animal health. The rearing and grazing of cows at the forest edge and in coconut plantations provide an ideal medium for the growth and development of flies. This study aimed to identify the diversity and abundance of fly species found on cows grazing in two habitat types: forest edge habitat and coconut plantation,located at the Tangkoko Nature Reserve in North Sulawesi, Indonesia. The study was conducted from April 2021 to June 2021 using 24 Ongole Crossbred cows including three adult males and three adult females (250-300 kg) and three males and three female calves (60-75 kg) in each habitat. Flies were collected using two fly nets that were swung along the cows in each habitat type with ten swings. The flies collected were identified based on morphology. A total of 6,982 flies were collected and identified to the following taxonomic groups: Muscidae family (Haematobia exigua 91.21%, Stomoxys calcitrans 1.65%, Musca crassirostris 0.67%, S. indicus 0.54%, S. sitiens 0.42%, and Musca domestica 0.11%), and Tabanidae family (Tabanus factiosus 4.91%, Tabanus striatus 0.47%, and Chrisops sp. 0.01%). The abundance of Haematobia exigua in the coconut plantation habitat was higher than in the forest edges, while the number of T. factiosus at the forest edges was higher than in the coconut plantations. Our results confirm that the presence of a variety of fly species and their abundance depends part on the grazing habitat of the cows. Further study of fly species diversity and pathogen status is critical to provide epidemiological data needed to develop control strategies to prevent the emergence of zoonotic diseases.